3D printing phosphoric acid pyrophosphate positive electrode material and preparation method and application thereof

The 3D printing of phosphate pyrophosphate electrodes addresses uneven coatings and structural issues in traditional methods, resulting in more uniform and stable sodium ion battery electrodes with improved energy density and stability.

CN119153649APending Publication Date: 2024-12-17CHANGDE COSPOWERS NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271015.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional coating processes for sodium ion battery electrode materials result in uneven coatings, difficulty in controlling the proportion of active substances, and structural deformations, affecting energy density, cycle performance, and overall battery performance.

Method used

A 3D printing method is employed to prepare phosphate pyrophosphate positive electrodes, involving the design of a printing model, blending of active materials with conductive agents and binders, printing on a substrate, and heat-treating the electrode material, using specific parameters and substrates to achieve uniformity and density.

Benefits of technology

The 3D printed electrodes exhibit improved uniformity, reduced internal resistance, enhanced energy density, and better mechanical stability, with a simpler and faster preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153649A_ABST
    Figure CN119153649A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printing phosphoric acid pyrophosphate positive electrode material and a preparation method and application thereof, and belongs to the technical field of sodium ion battery electrodes. The preparation method comprises the following steps: uniformly mixing a phosphoric acid pyrophosphate active material, a conductive agent, a binder and a solvent in proportion, putting the mixture into a 3D printer for printing to prepare a phosphoric acid pyrophosphate composite positive electrode material, and carrying out heat treatment on the phosphoric acid pyrophosphate composite positive electrode material to obtain the phosphoric acid pyrophosphate positive electrode material. The pyrophosphate positive electrode material prepared through 3D printing is more stable in structure and more uniform in surface, and the problems that the process is tedious and coating is not uniform when the pyrophosphate positive electrode material is prepared through a traditional coating mode are solved. In addition, the process flow for preparing the battery electrode by using the 3D printing technology is simpler and quicker, and the production cost can be reduced. The pyrophosphate positive electrode material prepared by the invention is widely applied to the technical field of sodium ion battery electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion battery positive electrodes, and in particular relates to a 3D printed phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium resources have the advantages of abundant reserves in the earth's crust and oceans, low cost and high theoretical capacity (120-170Wh / kg). Therefore, sodium-ion batteries have become one of the most promising technologies in the field of large-scale energy storage and are receiving more and more attention. x M y (PO4) m (P2O7) n (x>0, y>0, m>0, n>0), where M represents alkali metal ions, and is safer than other sodium ion positive electrode materials (such as NaFePO4, Na2FeP2O7, etc.). Among them, Na4Fe3(PO4)2P2O7 (NFPP) has a theoretical capacity of 129mAh / g. After modification and optimization, its single-phase volume change is only about 4% during the process of sodium ion insertion and extraction (doi.org / 10.1021 / cm4013816). Its scientific research and application value have been favored by the industry. However, at present, the production and manufacturing of sodium ion battery electrode materials are still prepared by traditional coating process. Unfortunately, there are also some problems in the preparation of pole pieces by traditional coating process: (1) The pole piece coating is uneven, which affects the sodium ion diffusion rate; (2) The proportion of effective active substances in the battery electrode is difficult to control, resulting in great difficulties in improving the energy density and cycle performance of the electrode material; (3) The prepared electrode structure is easy to deform, thus affecting the overall performance test of the battery. In view of this, it is urgent to invent a new technology for preparing sodium ion positive electrode materials and positive electrode sheets to solve the above problems.

[0003] As we all know, 3D printing technology is a very representative advanced battery preparation technology. There are many advantages to preparing battery electrodes through 3D printing technology. First, 3D printing technology has the characteristics of precise and diverse structure and rapid molding. It can flexibly control the structural dimensions of battery electrodes, thereby providing higher energy density and power density. Second, the battery electrodes prepared by 3D printing technology have tighter and more uniform contact, which can effectively shorten the sodium ion transmission and diffusion distance, reduce its internal resistance, and ensure that the prepared battery electrodes can improve their energy density without sacrificing the power density of the battery electrode. Therefore, the use of 3D printing technology to prepare uniform, dense, and high-performance sodium ion positive electrode materials has become a major trend in future commercial development. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned problems existing in the background technology and to provide a 3D printed phosphate pyrophosphate positive electrode material and a preparation method and application thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a 3D printed phosphoric acid pyrophosphate positive electrode material, the method comprising:

[0007] (1) Design a printing size model of the battery electrode according to actual application requirements, import the model into a 3D printer, and set relevant printing parameters;

[0008] (2) Evenly blending the active material, conductive agent, binder and solvent in proportion to prepare a battery electrode slurry;

[0009] (3) placing the electrode slurry in step (2) into a 3D printer and printing on a printing substrate to obtain a phosphate pyrophosphate positive electrode material;

[0010] (4) heat-treating the phosphate pyrophosphate positive electrode material obtained in step (3), and cooling to obtain the phosphate pyrophosphate positive electrode material.

[0011] Furthermore, in step (2), the active material is phosphate pyrophosphate, the chemical formula of which is Na x M y (PO4) m (P2O7) n or / and Na x M y (PO4) m (P2O7) n / X, X element exists on the surface or / and the bulk of the phosphate pyrophosphate, wherein x>0, y>0, m>0, n>0, M represents an alkali metal ion, including one or more of Fe, Co, Mn, Ge, Ni, Mg, Cu, Ca, Ti, and X represents one or more of carbon (C), nitrogen (N), sulfur (S) and the like, preferably Na x M y (PO4) m (P2O7) n / C, but is not limited to this.

[0012] Furthermore, in step (2), the conductive agent is one or more of carbon nanotubes, graphene oxide, graphene, conductive carbon black, and acetylene black, preferably graphene oxide; the binder is one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), sodium alginate, and polyacrylic acid (PAA), preferably polyvinylidene fluoride (PVDF).

[0013] Furthermore, in step (2), the solvent is one or more of deionized water, N-methyl-2-pyrrolidone (NMP), ethanol, dimethyl carbonate (DMC), ethylene carbonate (EC), and propylene carbonate (PC), preferably N-methyl-2-pyrrolidone (NMP).

[0014] Furthermore, in step (2), the mass percentages of the active material, conductive agent and binder are 30% to 95%, 1% to 35% and 1% to 35% respectively, the amount of solvent is adjusted according to actual conditions, and the solid content of the slurry is 35% to 75%.

[0015] Furthermore, in step (3), the printing substrate is one of aluminum foil, carbon-coated aluminum foil, and polytetrafluoroethylene film, preferably carbon-coated aluminum foil.

[0016] Furthermore, in step (3), the printing thickness of the electrode slurry on the printing substrate ranges from 8 micrometers to 1 millimeter, preferably from 100 micrometers to 400 micrometers.

[0017] Furthermore, in step (4), the heat treatment temperature is 50-900° C., the time is 1-8 hours, and the atmosphere is one or more of air, oxygen, nitrogen, argon or hydrogen.

[0018] A phosphoric acid pyrophosphate positive electrode material prepared by the above preparation method.

[0019] A phosphoric acid pyrophosphate positive electrode material prepared by the above preparation method is used in a sodium ion battery, which includes a positive electrode, an electrolyte, and a negative electrode. The positive electrode is the 3D printed phosphoric acid pyrophosphate positive electrode material prepared above.

[0020] The beneficial effects of the present invention compared to the prior art are:

[0021] (1) The phosphate pyrophosphate positive electrode material prepared by 3D technology has a more uniform and dense morphology, which can effectively shorten the sodium ion transmission diffusion distance and reduce its internal resistance. On the other hand, it can flexibly prepare battery electrodes according to needs. At the same time, this technology can regulate the structure and size of the sodium ion positive electrode material, thereby flexibly controlling its energy density.

[0022] (2) The phosphate pyrophosphate positive electrode material prepared by 3D technology has an integrated preparation process that is simpler and faster, with higher material utilization rate, which improves the preparation efficiency while avoiding the cumbersome problems of the traditional coating preparation process.

[0023] (3) The pyrophosphate cathode material prepared using 3D technology has good mechanical stability, which helps to maintain the structural integrity of the battery electrode during battery cycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a graph of capacity retention after 100 cycles at 0.5C rate in Example 3 of the present invention;

[0025] Figure 2 is a capacity curve diagram of 100 cycles at 0.5C rate in Example 5 of the present invention;

[0026] Figure 3 It is a simplified flow chart of the preparation of 3D printed batteries in Examples 1-6 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present application is further explained in conjunction with the following embodiments. It should be clear that the embodiments described here are only for further illustrating the present application and do not constitute a limitation on the present application.

[0028] The phosphoric acid pyrophosphate cathode material prepared by 3D printing in the present invention has a more stable structure and a more uniform surface, which solves the problems of cumbersome process and uneven coating in the preparation of phosphoric acid pyrophosphate cathode materials by traditional coating methods. In addition, the process flow of preparing battery electrodes using 3D printing technology is simpler and faster, which is conducive to reducing production costs. The phosphoric acid pyrophosphate cathode material prepared by the present invention is widely used in the field of sodium ion battery electrode technology.

[0029] Example 1

[0030] A method for preparing a 3D printed sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 (NFPP) cathode material specifically comprises the following steps:

[0031] (1) Design a printing size model of the battery electrode according to actual application requirements, import the model into a 3D printer, and set relevant printing parameters;

[0032] (2) The active material, conductive agent, binder and solvent are uniformly mixed in corresponding proportions to prepare a battery electrode slurry; the active material is sodium ferric pyrophosphate; the conductive agent is graphene oxide; the binder is PVDF; the ratio is 60wt%:20wt%:20wt%; and the mass proportion of the solvent is adjusted according to actual conditions, and there is usually no special limitation.

[0033] (3) placing the electrode slurry in step (2) into a 3D printer and printing on aluminum foil to obtain a composite phosphate pyrophosphate positive electrode material, with a printing thickness of 200 μm, a temperature of 25±5° C., and a relative humidity of ≤30% RH;

[0034] (4) The sodium iron phosphate pyrophosphate composite positive electrode material printed by 3D in step (3) is subjected to a heat treatment operation, and after cooling, a 3D printed phosphate pyrophosphate positive electrode material is obtained. The heat treatment time is 1 hour and the temperature is 200°C.

[0035] Performance Testing:

[0036] 1. Cyclic voltammetry test: CV test was performed using CHI660E electrochemical workstation (Shanghai Chenhua), and performance test was performed using a three-electrode system. In this process, the voltage scanning range was between 1.5-3.9V, the scanning rate was 0.3mV / s, and the termination voltage was 1.5V.

[0037] 2. Charge and discharge and cycle rate performance test: With the help of the CT2001A Blue Electric test instrument under Wuhan Blue Electric Technology Co., Ltd., the long cycle performance and rate performance of the assembled battery are tested.

[0038] Example 2

[0039] The difference from Example 1 is that the active material in step (2) is carbon-coated modified sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 / C.

[0040] Example 3

[0041] The difference from Example 1 is that the active material in step (2) is Na4Fe3(PO4)2P2O7 / C, and the ratio of the active material, the conductive agent, and the binder is 50wt%:20wt%:30wt%; Figure 1 , which is the capacity retention curve after 100 cycles at 0.5C rate.

[0042] Example 4

[0043] The difference from Example 1 is that the active material in step (2) is Na4Fe3(PO4)2P2O7 / C; the ratio of the active material, the conductive agent and the binder is 50wt%:20wt%:30wt%; and the 3D printing substrate in step (3) is carbon-coated aluminum foil.

[0044] Example 5

[0045] The difference from Example 1 is that the active material in step (2) is Na4Fe3(PO4)2P2O7 / C; the ratio of the active material, the conductive agent, and the binder is 50wt%:20wt%:30wt%; the 3D printing substrate in step (3) is carbon-coated aluminum foil; the heat treatment time in step (4) is 2h and the temperature is 300°C; Figure 2 , which is the capacity curve after 100 cycles at 0.5C rate.

[0046] Example 6

[0047] The difference from Example 1 is that the active material in step (2) is Na4Fe3(PO4)2P2O7 / C; the ratio of the active material, the conductive agent and the binder is 50wt%:20wt%:30wt%; the 3D printing substrate in step (3) is carbon-coated aluminum foil; the heat treatment time in step (4) is 3h and the temperature is 500°C.

[0048] The 3D printed sodium iron phosphate pyrophosphate cathode material was heat treated, cooled to room temperature and cut into electrode sheets with a diameter of 14 mm. The electrochemical performance of the assembled button battery was tested. The results are as follows:

[0049] The test results of Examples 1-6 of the present invention are shown in Table 1.

[0050] Table 1

[0051] Current density Capacity mAh / g Cycle times Capacity retention rate Example 1 0.5C 95.10 100 81.61% Example 2 0.5C 105 100 90.30% Example 3 0.5C 101.54 100 95.51% Example 4 0.5C 110.12 100 95.1% Example 5 0.5C 90.76 100 97.05% Example 6 0.5C 107.93 100 96.5%

[0052] It can be seen from the test results of the above embodiment that by adjusting the preparation parameters, a discharge specific capacity of 90.76 mAh / g can be achieved, and the capacity retention rate after 100 cycles under 0.5C rate test conditions is 97.05%. Figure 3 In the preparation process of 3D printed sodium iron pyrophosphate positive electrode sheets, the discharge specific capacity of the positive electrode material can also be improved by adjusting the drying and heat treatment temperatures.

[0053] The above-listed embodiments are only intended to illustrate the technical solutions of the present application and do not constitute a limitation thereto; even if the present application is explained in detail based on the above-mentioned embodiments, ordinary technicians in this field should also know that they can still modify the technical solutions recorded in the above-mentioned embodiments, optimize the experimental results, or implement equivalent replacements for some of the technical features therein: however, these modifications or replacements should not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of each embodiment of the present application, but should be included in the protection scope of the present application, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a 3D printed phosphoric acid pyrophosphate positive electrode material, characterized in that: The method is: (1) Design a printing size model of the battery electrode according to actual application requirements, import the model into a 3D printer, and set relevant printing parameters; (2) Evenly blending the active material, conductive agent, binder and solvent in proportion to prepare a battery electrode slurry; (3) placing the electrode slurry in step (2) into a 3D printer and printing on a printing substrate to obtain a phosphate pyrophosphate positive electrode material; (4) heat-treating the phosphate pyrophosphate positive electrode material obtained in step (3), and cooling to obtain the phosphate pyrophosphate positive electrode material.

2. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (2), the active material is phosphate pyrophosphate, the chemical formula of which is Na x M y (PO4) m (P2O7) n or / and Na x M y (PO4) m (P2O7) n / X, X element exists on the surface and / or in the bulk of phosphate pyrophosphate, wherein x>0, y>0, m>0, n>0, M represents an alkali metal ion, including one or more of Fe, Co, Mn, Ge, Ni, Mg, Cu, Ca, and Ti, and X represents one or more of elements such as carbon (C), nitrogen (N), and sulfur (S).

3. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (2), the conductive agent is one or more of carbon nanotubes, graphene oxide, graphene, conductive carbon black, and acetylene black; the binder is one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), sodium alginate, and polyacrylic acid (PAA).

4. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (2), the solvent is one or more of deionized water, N-methyl-2-pyrrolidone (NMP), ethanol, dimethyl carbonate (DMC), ethylene carbonate (EC), and propylene carbonate (PC).

5. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (2), the mass percentages of the active material, the conductive agent, and the binder are 30% to 95%, 1% to 35%, and 1% to 35%, respectively.

6. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (3), the printing substrate is one of aluminum foil, carbon-coated aluminum foil, and polytetrafluoroethylene film.

7. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (3), the printing thickness of the electrode slurry on the printing substrate ranges from 8 microns to 1 millimeter.

8. A method for preparing a 3D printed phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: In step (4), the heat treatment temperature is 50-900° C., the time is 1-8 hours, and the atmosphere is one or more of air, oxygen, nitrogen, argon or hydrogen.

9. A phosphate pyrophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. A phosphate pyrophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 8, which is used in a sodium ion battery.